Identification of a cyclic-di-GMP-modulating response regulator that impacts biofilm formation in a model sulfate reducing bacterium - Rajeev, Lara; Luning, Eric G.; Altenburg, Sara; Zane, Grant M.; Baidoo, Edward E. K.; Catena, Michela; Keasling, Jay D.; Wall, Judy D.; Fields, Matthew W.; Mukhopadhyay, Aindrila (Frontiers in Microbiology, 2014)
We surveyed the eight putative cyclic-di-GMP-modulating response regulators (RRs) in Desulfovibrio vulgaris Hildenborough that are predicted to function via two-component signaling. Using purified proteins, we examined cyclic-di-GMP (c-di-GMP) production or turnover in vitro of all eight proteins. The two RRs containing only GGDEF domains (DVU2067, DVU0636) demonstrated c-di-GMP production activity in vitro. Of the remaining proteins, three RRs with HD-GYP domains (DVU0722, DVUA0086, and DVU2933) were confirmed to be Mn2+-dependent phosphodiesterases (PDEs) in vitro and converted c-di-GMP to its linear form, pGpG. DVU0408, containing both c-di-GMP production (GGDEF) and degradation domains (EAL), showed c-di-GMP turnover activity in vitro also with production of pGpG. No c-di-GMP related activity could be assigned to the RR DVU0330, containing a metal-dependent phosphohydrolase HD-OD domain, or to the HD-GYP domain RR, DVU1181. Studies included examining the impact of overexpressed cyclic-di-GMP-modulating RRs in the heterologous host E. coli and led to the identification of one RR, DVU0636, with increased cellulose production. Evaluation of a transposon mutant in DVU0636 indicated that the strain was impaired in biofilm formation and demonstrated an altered carbohydrate:protein ratio relative to the D. vulgaris wild type biofilms. However, grown in liquid lactate/sulfate medium, the DVU0636 transposon mutant showed no growth impairment relative to the wild-type strain. Among the eight candidates, only the transposon disruption mutant in the DVU2067 RR presented a growth defect in liquid culture. Our results indicate that, of the two diguanylate cyclases (DGCs) that function as part of two-component signaling, DVU0636 plays an important role in biofilm formation while the function of DVU2067 has pertinence in planktonic growth.